Official Bulletin No. 6, Walthamstow Central Executive Strike Committee, 12 May 1926 (Walthamstow)
1926-05-12 "Official Bulletin No. 6, Walthamstow Central Executive Strike Committee, 12 May 1926" [g0244001.jpg], 12 May 1926 Local Organisation